Resisting resistance

In the given diagram, if the equivalent resistance between the points A and B can be written as R = a R + b r c + d R r R' = \frac{aR + br}{c + \frac{dR}r} . What is a + b + c + d a+b+c+d ?

Note that the expression is in its simplest form.


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jun 27, 2015

Transform the left (A-side) delta connection into a star connection, then we have:

R = R r R + 2 r + ( r 2 R + 2 r + R ) ( R r R + 2 r + r ) = R r R + 2 r + r 2 + 2 R r + R 2 R + 2 r R r + R r + 2 r 2 R + 2 r = R r R + 2 r + ( R + r ) 2 R + 2 r 2 r ( R + r ) R + 2 r = R r R + 2 r + ( R + r ) 2 R + 2 r × 2 r ( R + r ) R + 2 r ( R + r ) 2 R + 2 r + 2 r ( R + r ) R + 2 r = R r R + 2 r + 2 r ( R + r ) 3 ( R + 2 r ) 2 ( R + r ) ( R + 3 r ) R + 2 r = R r R + 2 r + 2 r ( R + r ) 2 ( R + 2 r ) ( R + 3 r ) = r R + 2 r ( R + 2 ( R + r ) 2 R + 3 r ) = r R + 2 r ( R 2 + 3 R r + 2 R 2 + 4 R r + 2 r 2 R + 3 r ) = r ( 3 R 2 + 7 R r + 2 r 2 ) ( R + 2 ) ( R + 3 r ) = r ( 3 R + r ) ( R + 2 r ) ( R + 2 ) ( R + 3 r ) = r ( 3 R + r ) R + 3 r = 3 R + r 3 + R r \begin{aligned} R' & = \frac{Rr}{R+2r} + \left(\frac{r^2}{R+2r}+R\right) || \left(\frac{Rr}{R+2r}+r \right) \\ & = \frac{Rr}{R+2r} + \frac{r^2+2Rr+R^2}{R+2r} || \frac{Rr+Rr+2r^2}{R+2r} \\ & = \frac{Rr}{R+2r} + \frac{(R+r)^2}{R+2r} || \frac{2r(R+r)}{R+2r} \\ & = \frac{Rr}{R+2r} + \frac {\frac{(R+r)^2}{R+2r} \times \frac{2r(R+r)}{R+2r}} {\frac{(R+r)^2}{R+2r} + \frac{2r(R+r)}{R+2r}} \\ & = \frac{Rr}{R+2r} + \frac {\frac{2r(R+r)^3}{(R+2r)^2}} {\frac{(R+r)(R+3r)}{R+2r}} \\ & = \frac{Rr}{R+2r} + \frac {2r(R+r)^2}{(R+2r)(R+3r)} \\ & = \frac{r}{R+2r}\left(R + \frac {2(R+r)^2}{R+3r} \right) \\ & = \frac{r}{R+2r}\left(\frac {R^2+3Rr + 2R^2+4Rr+2r^2}{R+3r} \right) \\ & = \frac {r(3R^2+7Rr+2r^2)}{(R+2)(R+3r)} = \frac {r(3R+r)(R+2r)}{(R+2)(R+3r)} \\ & = \frac {r(3R+r)}{R+3r} = \frac {3R+r}{3+\frac{R}{r}} \end{aligned}

a + b + c + d = 3 + 1 + 3 + 1 = 8 \Rightarrow a + b + c + d = 3+1+3+1 = \boxed{8}

You are a genius basher sir ! Your latex skills are amazing too !

Venkata Karthik Bandaru - 5 years, 11 months ago
Somsubhra Ghosh
Jun 24, 2015

This is a simple case of an unbalanced Wheatstone bridge. To find the equivalent resistance of the circuit, let us connect a battery of pd, V betn the points A and B as shown in the figure.

Applying Kirchhoff's voltage rule to loop 1, -(I - I')r - I"r + I'R = 0

For loop 2, -(I - I' - I")R + (I' + I")r + I"r =0

For loop 3, V - I'R - (I' + I")r =0

Solving the three equations, we get I = V (3+ R/r) / (3R + r)

Comparing this with I = V/R', we get R' = (3R + r)/(3+ R/r) Hence the result.

Don't mind but have u given it from irodov??

Shyambhu Mukherjee - 5 years, 6 months ago

Log in to reply

You can find the same problem with capacitors in the worked out examples of H.C. Verma.

Soumava Pal - 5 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...